Levers for alleviating poverty in forests - Hajjar, R.; Newton, P.; Ihalainen, Markus; Agrawal, A.; Alix-Garcia, J.; Castle, S.E.; Erbaugh, J.T.; Gabay, M.; Hughes, K.; Mawutor, S.; Pacheco, P.; Schoneveld, George C.; et al. (Elsevier, 2021)
An extensive set of policies, programmes, technologies and strategies have been implemented in the forest sector. Collectively, these ‘levers’ cover a diverse range of approaches, at a variety of scales and are governed by many different stakeholders. It is important for decision-makers to understand which levers might be most useful in achieving poverty alleviation. This paper seeks to answer the question: which forest management policies, programmes, technologies and strategies have been effective at alleviating poverty? We studied 21 different rights-based, regulatory, market and supply chain, and forest and tree management levers for which we could identify a plausible theory of change of how implementation of that lever might alleviate poverty. For every lever we: define and describe the lever; describe the logic or theory of change by which the lever might plausibly be expected to alleviate poverty; summarize the available evidence showing how the lever has alleviated poverty; and discuss the variables that explain heterogeneity in outcomes. Overall, we found limited evidence of these levers being associated with reducing poverty (i.e. moving people out of poverty). Some of the strongest evidence for poverty reduction came from ecotourism, community forest management, agroforestry and, to a lesser extent, payments for ecosystem services (PES). However, we found substantial, varied and context-dependent evidence of several levers being associated with mitigating poverty (i.e. by improving well-being). A multitude of cases showing positive outcomes for poverty mitigation came from community forest management, forest producer organisations, small and medium forest enterprises, PES, and tree crop contract production. A combination of more rigorous and long-term research designs, along with examinations of the cost-effectiveness of different levers, would go a long way to contributing to the design of effective interventions for poverty alleviation.